Pencegahan Hipertensi Melalui Edukasi di Sungai Bangkong, Pontianak Kota, Kota Pontianak, Kalimantan Barat - Namira Adha; Dyah Utari; Fandita Tonyka M (Jurnal Pengabdian Kepada Masyarakat Kalam, 2022)
Hypertension is one non-communicable disease whose prognosis is influenced by lifestyle. A healthy lifestyle is influenced by one's knowledge. Increased knowledge is the key to prevention and management of hypertension. This community service aims to increase public knowledge about the prevention and management of hypertension. From the evaluation results, it was found that there was an increase in knowledge of 35% after health promotion interventions through counseling. It is hoped that similar interventions can be carried out routinely and to the wider community